Compositional changes of human hair melanin resulting from bleach treatment investigated by nanoscale secondary ion mass spectrometry. Issue 4 (8th February 2014) - Kojima, Toru; Yamada, Hiromi; Isobe, Mitsuru; Yamamoto, Toshihiko; Takeuchi, Miyuki; Aoki, Dan; Matsushita, Yasuyuki; Fukushima, Kazuhiko
<x xml:space="preserve">Abstract</x> Background/purpose It is important to understand the influence of bleach treatment on human hair because it is one of the most important chemical treatments in hair cosmetic processes. A comparison of the elemental composition of melanin between virgin hair and bleached hair would provide important information about the structural changes of melanin. To investigate the elemental composition of melanin granules in virgin black hair and bleached hair, these hair cross‐sections are analyzed by using a nanoscale secondary ion mass spectrometry (NanoSIMS). Methods The virgin black hair and bleached hair samples were embedded in resin and smooth hair cross‐sections were obtained using an ultramicrotome. NanoSIMS measurements were performed using a Cs+ primary ion beam to detect negative secondary ions. Results More intensive 16O− ions were detected from the melanin granules of bleached hair than from those of virgin black hair in NanoSIMS 16O− ion image. In addition, it was indicated that 16O− ion intensity and 16O‐/12C14N− ion intensity ratio of melanin granules in bleached hair were higher than those in virgin black hair. Conclusion Nanoscale secondary ion mass spectrometry analysis of the cross‐sections of virgin black hair and bleached hair indicated that the oxygen content in melanin granules was increased by bleach treatment.